Strategi Pengembangan Industri Usaha Tahu Berbasis Islamic Business Model Canvas: (Studi Kasus: UD. Marni Kota Tebing Tinggi) - Nurkomaria Nurkomaria; Tri Inda Fadhila Rahma; Juliana Nasution (Jurnal Riset Akuntansi, 2025)
This study analyzes the development strategy of UD. Marni's tofu business in Tebing Tinggi City using the Islamic Business Model Canvas (BMC Islamic) with a qualitative phenomenological approach through a case study. Data were obtained from in-depth interviews with owners and workers and participant observation of the production process, which were mapped into nine BMC Islamic blocks based on sharia principles such as fairness, halalness, and blessings. Results indicate the current business model relies on daily production of fresh fried tofu for local vendors and households, with strengths in authentic taste and personal relationships, but challenges related to raw material fluctuations and limited marketing. Development strategies include MUI halal certification, sharia digital marketing via WhatsApp/Instagram, diversification of packaging variants, musyarakah partnerships with suppliers, and cost optimization, including 2.5% zakat, which is projected to increase turnover by 20-30% while maintaining Islamic values. This research contributes to strengthening sharia-compliant tofu MSMEs in Tebing Tinggi for sustainable growth.